Pengaruh Kitab Adiparwa dan Serat Purwakandha terhadap Pertunjukan Wayang Kulit Gaya Yogyakarta Lakon Abimanyu Lair: Kajian Intertekstualitas - Mulyono, Sri (Institut Seni Indonesia Yogyakarta, 2022)
AbstractThis study aims to see the intertextual relationship between the Yogyakarta-style puppet performance of Abimanyu Lair by Ki M.L. Cermasudira and the story of Abhimanyu’s birth in Serat Purwakandha and the book of Adiparwa. For the purpose, a literature study about the birth was carried out, summarized, followed by a comparative and intertextual study using Joko Pradopo’s framework. In fact, transformation, continuity, and discontinuity occurred in the intertextual process. Transformation occurred in form and language. The book of adiparwa in form of ancient Javanese prose and Serat Purwakandha in form of New Javanese macapat songs transformed into a Yogyakarta style purwa puppet performance in puppetry language. Continuity could be seen in the theme similarity, namely birth. The continuity of Serat Purwakandha to puppet performance colud be seen at the event that Abhimanyu’s birth was always assisted by angels and gods; it was always interrupted by the king of the other world; Krishna always cared for Sembadra, Abimanyu, and the Pandavas; the name of Abimanyu was given by Bima. Discontinuity includes: differences in the arrangement of scenes, in which the arrangement of the puppet performance scenes was bound to the conventions of the patterns of puppet performance while the others were free; the difference in characters and settings in the three texts, which texts the newest text had more characters and settings. The deviation of ideas and story development was found in the emergence of the wahyu widayat story and Bima’s role in the Yogyakarta style puppet performance as an effort to put Abimanyu as the central queen Java land (‘ancestor of the kings of Java’) and Bima’s role in Javanese religious and Sufism system, namely through the palace revelation.In conclusion Abimanyu Lair puppet performance in a Yogyakarta-style puppet performance as a representation of the courtiers of the Yogyakarta palace shows a relationship with Serat Purwakandha but far different from the book of Adiparwa.AbstrakPenelitian ini bertujuan melihat hubungan intertekstual antara pertunjukan wayang kulit gaya Yogyakarta lakon Abimanyu Lair sajian Ki M.L. Cermasudira dengan cerita kelahiran Abimanyu pada Serat Purwakandha dan kitab Adiparwa. Untuk mencapai tujuan tersebut dilakukan studi pustaka cerita kelahiran Abimanyu, meringkas cerita, dilanjutkan studi komparasi, dan intertekstual model Joko Pradopo. Dalam prosesintertekstual, terjadi transformasi, kontinuitas, dan diskontiunitas. Transformasi terlihat pada transformasi bentuk dan bahasa. Kitab adiparwa berbentuk prosa berbahasa jawa kuna dan Serat Purwakandha berbentuk tembang macapat berbahasa jawa baru bertransformasi menjadi pertunjukan wayang kulit purwa gaya Yogyakarta berbahasa pedalangan. Kontinuitas terlihat pada persamaan tema yakni kelahiran. Kontinuitas Serat Purwakandha ke pertunjukan wayang terlihat pada peristiwa kelahiran Abimanyu selalu dibantu bidadari dan dewa; kelahiran Abimanyu selalu diganggu raja sabrang; Kresna selalu peduli kepada Sembadra, Abimanyu, dan Pandawa; nama Abimanyu diberikan oleh Bima. Diskontinuitas meliputi: perbedaan susunan adegan, dimana susunan adegan pertunjukan wayang kulit terikat konvensi pola bangunan lakon wayang sedang yang lain bersifat bebas; perbedaan tokoh dan setting pada ketiga teks, dimana teks yang lebih muda memiliki jumlah tokoh dan setting lebih banyak. Penyimpangan ide dan pengembangan cerita terdapat pada munculnya kisah wahyu widayat dan peran Bima dalam pertunjukan wayang kulit purwa gaya Yogyakarta sebagai upaya mendudukkan Abimanyu sebagai pancer ratu tanah Jawa (‘leluhur raja-raja Jawa’) dan peranan Bima dalam system religious dan tasawuf Jawa, yakni melalui wahyu karaton. Berdasarkan analisis yang dilakukan diperoleh hasil bahwa lakon Abimanyu Lair dalam pertunjukan wayang kulit gaya Yogyakarta sebagai representasi pakeliran abdi dalem keraton Yogyakarta menunjukkan adanya hubungan dengan teks sebelumnya yaitu Serat Purwakandha namun jauh dari kitab Adiparwa.